Enabling innovation in large companies using innovation hubs, corporate accelerators or incubators: a practical example of Deutsche Lufthansa AG - Goerdes, Christian (2021)
To overcome the obstacles to innovation, large companies have increasingly created corporate innovation hubs, accelerators or incubators. This study uses the example of the Deutsche Lufthansa Group to illustrate their main considerations, opportunities and challenges. It provides first the set-up, design and evaluation of Lufthansa’s innovation hub model and then derives six key implications other companies should acknowledge when creating a respective hub. One of them is of particular importance: Since ideas that were initially developed and fostered by an innovation hub often lose ground thereafter, each innovation hub should establish a clear “follow up” plan as an inevitable strategic element.